Understanding Magic - The Effects of Storytelling Traditions on Intergenerational Bonding - Mészáros Zoltán Péter (2018)
The protagonist boy in Neil Gaiman’s The Ocean at the End of the Lane sets out to understand the world, make interpersonal relationships and solve his family problems relying on the storytelling traditions he is familiar with from fantastic stories and myths. Foregrounded by the metafictional tone of the narrative, these usual narrative conventions are challenged and present covertly in the story. Further complicates the realisation of traditions, like fairy-tale tropes or conventional story structures like Cambell’s Hero's Journey, the dominant presence of essential family relations and expectations as primary traditions before the storytelling ones. Characters are difficult to understand on the basis of archaic tropes and offer the possibility of different interpretations for generations based on the differences in their knowledge. A deep-reading analysis of the characters and their relations take into account the postmodern metafictional manner in which these storytelling traditions are implemented and looking out for different interpretations depending on the age and knowledge of the reader results in a peculiar range of representation. Making sense of the real world is supported by the understanding of storytelling traditions which remains a reliable source of support when unknown, original scenery is presented.